‘Trapped temporal horn’ of lateral ventricle in tuberculous meningitis - Sharma, Chandramohan (BMJ Publishing Group, 2014)
A young girl presented with a 1-month history of constitutional symptoms, headache and vomiting and 7-day history of left hemiparesis. Neuroimaging showed the ‘trapped temporal horn’ sign, suggestive of focal obstructive hydrocephalus at the foramen of Monro. Analysis of the cerebrospinal fluid and other investigations revealed a tubercular aetiology. The patient was managed with a ventriculoperitoneal shunt and antitubercular medications.